Implications of the transition from adaptation to resilience finance. (10th November 2017) - Barrett, Sam
Abstract : Adaptation finance is the generic term for resources used to assist institutions and populations addressing climate risks. As donors aim for adaptation at scale, a conceptual and practical transition is underway: first, policy framing concepts of 'adaptation' and 'vulnerability reduction' are yielding to 'resilience' as emphasis grows on theoretical frameworks for the design of 'resilient systems' particularly suitable for institutional change; second, the practice of adaptation increasingly takes the form of mainstreaming climate resilience that reforms ongoing development policy. This viewpoint documents emerging evidence that the conceptual and practical shift away from adaptation finance – towards what is more accurately termed 'resilience finance' – influences the objectives of policy, and perhaps most importantly, the actors privileged by policy. Resilience finance tends to raise the capacity of higher level government institutions, meaning that as funds increase, disproportionately fewer small-scale local/community-level projects directly benefit the poorest with highest exposure to adverse climate effects. Policy-makers need to ensure the poorest are privileged in the design of climate mainstreaming, through initiatives such as integrating climate resilience into social protection.